(untitled) (Muitas Vozes, 2023)
Antônio Candido on his Formação da literadura brasileira (2013), states that “there is in Alencar an implicit sociologist), as, in the majority of his romances Where profound themes happen, the narrative gains strenght because of the economic inequality between the characters that are presented, affecting the affectivity relationships between those characters. In Senhora (1875), one of the romances that deals in such themes, Alencar brings the conflict to the highest tension between the protagonists and, differently from others romantic romances, gets them in na equal footing. The goal of this paper is to discuss how José de Alencar observes and discusses the gender relationships from his time and making criticisms to the costums from his time, specially in what relates to the so common marriage by interests from century XIX. So, the presente paper aims, following the ideas from the authors like Candido (2013); Freyre (1996); Bosi (2006), dissert about the subversions from the gender relationships from the 1800’s through the construction of Aurélia, protagonista of Senhora, which has in the conscience of her actions in front rio de janeiro Society the driving force of the narrative.